The RANCANG BANGUN APLIKASI SELEKSI PERANGKAT DESA MENGGUNAKAN METODE COMPUTER ASSISTED TEST (CAT) BERBASIS WEB (Studi Kasus Desa Ketawang): Design And Build Application for Selection of Village Officials Using The CAT (Computer Assisted Test) Method Web-based (Case Study Of Ketawang Village) - Dita Septy Kurniasari Kurniasari (LPPM Universitas Merdeka Madiun, 2023)
Recruitment of village officials is an essential part of village development. Quality village governance positively impacts public services and overall village development. Absolutely, village officials must be people who has the high quality. However, there are often problems in recruiting village officials, such as limitations in processing information from prospective village officials. The election of village officials in Ketawang village is still done manually, using paper-based written tests. Based on these problems, a Web-Based Village Officials' Selection Information System has been successfully built, especialy for Ketawang Village. The system was built using the waterfall software development method and CodeIgniter framework. This system was built using the CAT (Computer Assisted Test) system model. This system was created to assist the committee in the village Official's selection activities more effectively and efficiently. Based on the test results, Black Box Testing produces an accuracy of up to 100%.